Biodegradation of petroleum sludge by Methylobacterium sp - Shamsul Harumain, Zakuan Azizi (2012)
A bacterium was isolated from sludge contaminated soil in petroleum refinery centre and tested for its ability to degrade hydrocarbon in petroleum sludge obtained from Shell Refinery Centre, Port Dickson, Negeri Sembilan. The isolate was tentatively identified as Methylobacterium sp. strain ZASH based on the partial 16s rRNA molecular phylogeny. The optimum condition for the strain to degrade petroleum sludge was characterized and quantified using GCFID. It was revealed that the bacterium degrade optimally between the temperature of 30°C to 35°C, pH 7 to 7.5, 0.5 to 1.5% (v/v) Tween 80 as surfactant source and at 1 to 2% (w/v) peptone as the nitrogen source. Gas chromatography analysis revealed that after 15 days, the Methylobacterium sp. strain ZASH was able to degrade 70% of hydrocarbons component of chain length C12-C36 found in petroleum sludge. It was also found that sawdust can be a good hydrocarbon adsorbent as its addition increase the hydrocarbon removal up to 99% removal.